Effect of national guidance on survival for babies born at 22 weeks’ gestation in England and Wales: population based cohort study - Bradley N Manktelow; Stavros Petrou; Elizabeth S Draper; Jennifer J Kurinczuk; Richard Lindley; Victoria Nesbitt; Alan C Fenton; Sanjay Salgia; Sarah E Seaton; Matthew Babirecki; Anita Mittal; Ahmed Hassan; et al. (BMJ Medicine)
Objectives To explore the effect of changes in national clinical recommendations in 2019 that extended provision of survival focused care to babies born at 22 weeks’ gestation in England and Wales.Design Population based cohort study.Setting England and Wales, comprising routine data for births and hospital records.Participants Babies alive at the onset of care in labour at 22 weeks+0 days to 22 weeks+6 days and at 23 weeks+0 days to 24 weeks+6 days for comparison purposes between 1 January 2018 and 31 December 2021.Main outcome measures Percentage of babies given survival focused care (active respiratory support after birth), admitted to neonatal care, and surviving to discharge in 2018-19 and 2020-21.Results For the 1001 babies alive at the onset of labour at 22 weeks' gestation, a threefold increase was noted in: survival focused care provision from 11.3% to 38.4% (risk ratio 3.41 (95% confidence interval 2.61 to 4.45)); admissions to neonatal units from 7.4% to 28.1% (3.77 (2.70 to 5.27)), and survival to discharge from neonatal care from 2.5% to 8.2% (3.29 (1.78 to 6.09)). More babies of lower birth weight and early gestational age received survival focused care in 2020-21 than 2018-19 (46% to 64% at <500g weight; 19% to 31% at 22 weeks+0 days to 22 weeks+3 days).Conclusions A change in national guidance to recommend a risk based approach was associated with a threefold increase in 22 weeks’ gestation babies receiving survival focused care. The number of babies being admitted to neonatal units and those surviving to discharge increased.